1967
DOI: 10.1084/jem.126.3.523
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Polymorphonuclear Leukocytes to Infertility in Uteri Containing Foreign Bodies

Abstract: The intrauterine contraceptive device is a potentially important factor in the world population problem, primarily became it provides an effective method of contraception that does not require continuous motivation on the part of the user. In addition, its cost is trivial, its insertion requires only a few minutes, and normal fertility returns quickly after its removal. There is also some reason (1, 2) to hope that the difficulties in its use, such as expulsions and rare pregnancies, can be overcome, since we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 17 publications
6
32
0
Order By: Relevance
“…In the majority of species studies so far an IUD induces a cellular (PMNL or macrophage) invasion of the uterine lumen, and this feature appears to be an important aspect of intrauterine contraception (see Greenwald, 1965;Parr, Schaedler & Hirsch, 1967;El Sahwi & Moyer, 1971;Cuadros & Hirsch, 1972;Bo, Krueger & Bartley, 1974;Myatt, Bray, Gordon & Morley, 1975). The present observations strongly support the view that in the mouse a silk IUD exerts its antifertility action principally by leucocyte-mediated degeneration of uterine embryos, and partly by retention of embryos in the oviduct.…”
Section: Discussionsupporting
confidence: 78%
“…In the majority of species studies so far an IUD induces a cellular (PMNL or macrophage) invasion of the uterine lumen, and this feature appears to be an important aspect of intrauterine contraception (see Greenwald, 1965;Parr, Schaedler & Hirsch, 1967;El Sahwi & Moyer, 1971;Cuadros & Hirsch, 1972;Bo, Krueger & Bartley, 1974;Myatt, Bray, Gordon & Morley, 1975). The present observations strongly support the view that in the mouse a silk IUD exerts its antifertility action principally by leucocyte-mediated degeneration of uterine embryos, and partly by retention of embryos in the oviduct.…”
Section: Discussionsupporting
confidence: 78%
“…These effects on the endometrium may reduce the subsequent viability of embryos managing to survive the toxic effects of the copper IUD and in this way explain the increased effective¬ ness of the copper IUD over the conventional inert IUD as reported by Zipper, Tatum, Pastene, Medel & Rivera (1969). On the other hand, Parr, Schaedler & Hirsch (1967) …”
Section: Discussionmentioning
confidence: 96%
“…Lysosomal enzymes such as /?-glucuronidase (Parr, 1969) and lysozyme (Parr, Schaedler & Hirsch, 1967) have been reported to be released into the uterine lumen of the rat during chronic leucocyte infiltration under the influence of intrauterine foreign bodies, but the concentration of leucocytes in the uterine lumen during a normal pregnancy does not appear to increase and would probably be detri¬ mental to the pregnancy if it did. There is a possibility, however, that prefer¬ ential release of certain lysosomal enzymes may occur from endometrial cells under the action of progesterone which is reported to decrease the stability of the lysosomal membrane (Weissman, 1969).…”
Section: Tions Discussionmentioning
confidence: 99%